Global nature, global culture - Franklin, Sarah; Lury, Celia; Stacey, Jackie (SAGE, 2000)
Understandings of globalization have been little explored in relation to gender or related concerns such as identity, subjectivity and the body. This book contrasts `the natural' and `the global' as interpretive strategies, using approaches from feminist cultural theory. The book begins by introducing the central themes: ideas of the natural; questions of scale and context posed by globalization and their relation to forms of cultural production; the transformation of genealogy; and the emergence of interest in definitions of life an life forms.
Keywords: feminismi; globalisaatio; ihminen; kulttuuri; kulttuurisosiologia; luonto; nuoret; feminism; globalisering; människan; kultur; kultursociologi; naturen; ungdomar